The impact of compressive force magnitude on the in vitro neutral zone range and passive stiffness during a flexion–extension range of motion test - Mamiko Noguchi; Chad E. Gooyers; Michael W.R. Holmes; Jack P. Callaghan (Cogent Engineering, 2015)
The objective of this work was to examine the influence of compressive force magnitude on a functional spinal unit’s (FSU) flexion–extension neutral zone measured during pure moment (PM) tests. Each porcine cervical FSU received four repeats of a PM test with 10, 300, 900 and 1,800 N of compressive force, in a randomized order. Increasing the magnitude of compression significantly decreased the neutral zone range (p < 0.001), while increasing passive stiffness (p < 0.001). The flexion limit at 10 N was significantly lower (p < 0.05) than the other loading conditions. Reporting the compressive force magnitude is important when posture is a standardized experimental factor considered in the design of in vitro spine biomechanics studies.